Short communicationAsymptomatic ST segment elevation in the recovery phase of the exercise stress test due to slow coronary flow - Sunbul, Murat; Erdogan, Okan; Sari, Ibrahim (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
covery phase; and c) ST segment elevation might be asymptomatic, as in the present case.Exercise-induced ST segment elevation without Q wave formation is rarely observed. Frequent causes are significant coronary stenosis, myocardial bridge and coronary vasospasm. Both exercise-induced ST segment elevation due to slow coronary flow and ST segment elevation in the recovery phase of the exercise stress test are very rare. We present a 49-year-old man with asymptomatic inferolateral ST segment elevation in the recovery phase of the exercise stress test due to slow coronary flow, which has not been reported previously. The learning points of the present paper are as follows: a) although significant coronary stenosis, myocardial bridge and coronary vasospasm are frequent causes of exercise-induced ST segment elevation, slow coronary flow might also cause it; b) one should keep in mind that ST segment elevation might also occur in the re